The Influence of Service and Facilities on Guests’ Interest at Padma Hotel Semarang - aishah, nurul; putra, aditya nova; wijayanti, ra. afera ratna; nurfitriana, siti (LIAISON JOURNAL OF BEST, 2024)
This study investigates the influence of service quality and facilities on guests' interest in Padma Hotel Semarang. Utilizing a quantitative approach, data were collected through surveys distributed to hotel guests. The analysis revealed that both service quality and facilities significantly impact guests' interest. Specifically, high-quality service and well-maintained facilities enhance guests' likelihood of choosing Padma Hotel Semarang over competitors. These findings provide valuable insights for hotel management aiming to attract and retain guests by emphasizing service excellence and facility improvements. Keywords: Service Quality, Hotel Facilities, Guest Interest, Hospitality Management, Padma Hotel Semarang